Escalation eaudiobook - Brown, Ryk (Frontiers Saga Part 2: Rogue Castes, 2020)
A cease-fire that has lasted seven years . . . Worlds half-destroyed that have been rebuilt anew . . . Friends and crewmates scattered light-years apart . . . New leaders that would be kings . . . The Jung threat has been renewed, in ways not imagined. It will take a new savior to inspire the masses, and once again lead those willing to fight against oppression. But who will the new savior be?